A Dual-Band Circularly Polarized Elliptical Patch Reflectarray Antenna for High-Power Microwave Applications - Gexing Kong; Xiangqiang Li; Qingfeng Wang; Jianqiong Zhang (IEEE Access, 2021)
The demand for multi-band high-power antennas, which have been rarely reported, becomes urgent in high-power microwave field. To meet the demand, a C/X dual-band high-power circularly polarized patch reflectarray antenna is proposed in this paper. Two main technologies are adopted to make the proposed antenna realize the high-power feature. Firstly, the elliptical patch with no abrupt structure is proposed to be the dual-band reflecting element to mitigate the electric field concentration. Secondly, the elliptical patches are proposed to be embedded into substrate to avoid the triple junction. The proposed dual-band reflecting element is designed by arranging two embedded elliptical patches with different sizes in a square lattice grid. The larger elliptical patch operates in C-band and the smaller one works in X-band. The elliptical patches are proposed to be rotated to realize continuous $360^{° }$ phase response in both bands. By optimizing the thickness of substrate, the element spacing, and the size of the patches, the dual-band element shows good reflection amplitude and phase response and low mutual coupling performance. An antenna prototype with the aperture size of 345 mm $×345$ mm is simulated and measured. The measured radiation results of the designed reflectarray antenna are in good agreement with simulations in both C-band and X-band. The measured gain of the antenna at 6.2 GHz is 24.6 dBi, and at 9.3 GHz is 27.8 dBi. Full-wave simulations show that the power capacity of the antenna at 6.2 GHz is about 10.2 MW, and at 9.3 GHz is about 3.9 MW in air condition. The low mutual coupling performance of the proposed antenna is verified both in element level and array level. All of the results show that the proposed antenna has the merits of high-power capacity, dual-band, and low mutual coupling.